Pemodelan ke Depan dan Inversi 2D Anomali Medan Magnet Berdasarkan Bentuk Prisma Sederhana - Yulia Ayu Setyawati; Supriyadi Supriyadi; Nurul Priyantari (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
The magnetic method use to determine the subsurface structure based on variations in the magnetic field on the earth's surface. interpretation of subsurface structures based on magnetic data includes parameters of depth, size, and magnetic susceptibility that can be obtained through modelling. The modelling carried out in this study includes forward modelling and inversion modelling for various parameters and also inversion modeling on WDMAM magnetic data in the Ijen area. Forward modelling results show that the value of the total magnetic field will be increase if the depth distance of the source of the anomaly is smaller, the susceptibility is greater, and the size of the anomalous object is getting bigger. Meanwhile, the results of the inversion modeling of synthetic data show a fairly good match between the subsurface structure and the initial synthetic model. The results of inversion modeling on WDMAM data in the Ijen area with coordinate boundaries 8˚30'- 8˚39' S and 113˚30' - 114˚30' E show the subsurface structure in the form of prism blocks with susceptibility dominated by mimeral magnetite, ilmenite , and pyrotite rocks at varying depths.